Profile of Head and Neck Cancer Patients at Hasan Sadikin Hospital in 2013-2018 - Nur Nathania; Yussy Afriani Dewi; Agung Dinasti Permana (PERHATI-KL, 2020)
ABSTRACTBackground: Head and neck cancer (HNC) is the 6th highest cancer worldwide. Risk factors include history of smoking, exposure of carcinogen, diet, oral hygiene, HPV and EBV infections, genetic, and alcohol consumption. Purpose: To identify the profile of HNC patients in the Department of Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) Hasan Sadikin General Hospital Bandung from 2013 to 2018. Method: A retrospective descriptive study was conducted in 2013-2018 in the Department of ORL-HNS Hasan Sadikin General Hospital, using total sampling method. Medical record of the patients were used as secondary data. Result: There were 2952 HNC patients consisted of 1689 males and 1263 females. Most of the subjects were graduated from elementary school (45.56%), with mean age 47.45 years old. The majority types of HNC were nasopharyngeal (31.20%), sinonasal (19.65%) and laryngeal (14.16%) carcinoma. The main histopathological types were undifferentiated carcinoma (47.15%) and squamous cell carcinoma (34.08%). The major risk factors were smoking and salted fish consumptions. Discussion: Unlike previous studies, our study found out that most HNC cases occurred in patients under the age of 30 years old. In this research, smoking was the highest risk factor of research subjects, followed by salted fish intake, mosquito burnt coils, and alcohol consumption. Nasopharyngeal carcinoma and stadium IV were the highest incidence of HNC, mostly found in male patients. Histopathologically, the dominant type was the undifferentiated carcinoma. Conclusion: Nasopharyngeal carcinoma was the main cancer type. The main histopathological type was undifferentiated carcinoma. The main risk factors were smoking and salted fish consumptions. ABSTRAKLatar belakang: Karsinoma kepala leher (KKL) merupakan keganasan terbanyak ke enam di dunia. Faktor risiko KKL antara lain riwayat merokok, paparan karsinogen, diet, kebersihan mulut, infeksi Human Papilloma Virus, Virus Epstein Barr, genetika, konsumsi alkohol. Tujuan: Untuk mengetahui profil penderita KKL di Departemen T.H.T-K.L Rumah Sakit Hasan Sadikin Bandung, tahun 2013- 2018. Metode: Penelitian deskriptif retrospektif dengan total sampling, pada periode 2013-2018 di Dept/KSM THT-KL RSUP Dr Hasan Sadikin. Rekam medis subjek penelitian digunakan sebagai data sekunder. Hasil: Terdapat 2.952 penderita KKL terdiri dari 1.689 laki-laki dan 1.263 perempuan. Mayoritas berpendidikan SD (45,56%), dengan rerata usia 47,45 tahun. Jenis KKL terbanyak karsinoma nasofaring (31,20%), sinonasal (19,65%), dan laring (14,16%). Karakteristik histopatologi terbanyak karsinoma tak berdiferensiasi (47,15%) dan karsinoma sel skuamosa (34,08%). Faktor risiko terbanyak merokok serta konsumsi ikan asin. Diskusi: Berbeda dengan penelitian sebelumnya, penelitian kami mendapatkan kasus KKL terbanyak didapati pada pasien di bawah usia 30 tahun. Didapatkan juga faktor risiko tertinggi adalah merokok, diikuti oleh mengonsumsi ikan asin, obat nyamuk bakar, dan minum alkohol. Angka kejadian KKL terbanyak adalah karsinoma nasofaring stadium IV, yang kebanyakan didapati pada pasien laki-laki. Secara histopatologi, tipe yang dominan adalah jenis karsinoma tak berdiferensiasi. Kesimpulan: Karsinoma nasofaring merupakan jenis KKL terbanyak. Jenis histopatologi terbanyak karsinoma tak berdiferensiasi. Faktor risiko KKL yang paling banyak ditemui yaitu merokok dan konsumsi ikan asin.